2013 IEEE Globecom Workshops (GC Wkshps) 2013
DOI: 10.1109/glocomw.2013.6825154
|View full text |Cite
|
Sign up to set email alerts
|

Back to normal? Impact of temporally increasing network disturbances on QoE

Abstract: Abstract-Brief episodes of network faults and performance issues adversely affect the user Quality of Experience (QoE). Besides damaging the current opinions of users, these events may also shape user's future perception of the service. Therefore, it is important to quantify the impact of such events on QoE over time. In this paper, we present our findings on the temporal aspects of user feedback to disturbances on networks. These findings are based on subjective user tests performed in the context of web brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…While the effect has been studied in smaller scale [42], [43], long term aspects are unclear. We hypothesized that age and previous experiences are related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effect has been studied in smaller scale [42], [43], long term aspects are unclear. We hypothesized that age and previous experiences are related.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been studied for short time frames for Web QoE [42] [43] in which it has been shown that after experiencing bad quality, participants reported a worse QoE even after the quality was back to normal. In relation to this, age has been shown to play a role in QoE, with elderly people reporting more problems in the usage of mobile phones, more skepticism towards new technology and a later adoption rate [44] (albeit differences in usage would often disappeared after elderly got more acquainted with the devices [45]).…”
Section: B Effect Of Context and User Factors On Qoementioning
confidence: 99%
“…This is likely to be explained by the interruption of the flow during an ongoing interaction. Shaikh et al [39] found for consecutive web pages that increasing the delay immediately reduces following retrospective judgments. If the delay is decreased afterwards again, following retrospective judgments remain affected.…”
Section: Perceived Quality Under Varying Performancementioning
confidence: 99%
“…Another study showed that the user-QoE drops significantly over time when the Page Load Time grows but it does not recover completely after the network problem is resolved [5]. In [6], authors show that the user satisfaction level breaks when waiting times exceed 10 seconds in a single session.…”
Section: Introductionmentioning
confidence: 99%